PENGARUH LINGKUNGAN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI KANTOR CAMAT ONOHAZUMBA KABUPATEN NIAS SELATAN - Novi Natalia Padang; Leniwati Hulu; Yurmanius Waruwu (LPPM Universitas Nias Raya, 2025)
The purpose of this study is to examine the effect of the work environment on employee work effectiveness at the Onohazumba Subdistrict Office, South Nias Regency, using a regression analysis method. The regression equation used is Y = 44.839 + (-0.095X). The results of the study show that (1) the work environment variable (X) has a positive and significant effect on employee work effectiveness (Y), with a t-value of 2.486 > t-table value of 1.701; therefore, the statistical hypothesis test is accepted. (2) The contribution of the influence is quite large, with a coefficient of determination (R²) of 0.352 or 35.2%, indicating that 35.2% of the variance in employee performance can be explained by the work environment variable, while the remaining 64.8% is attributed to other factors (ε). Thus, it can be concluded that the research hypothesis stating that there is an effect of the work environment (X) on employee work effectiveness (Y) is proven to be true. To improve employee work effectiveness, managerial interventions aimed at enhancing the work environment are important to achieve organizational goals